2025 IMJ Reviewers (Internal Medicine Journal, 2026)
The Royal Australasian College of Physicians (RACP) has recently issued a position statement titled 'Using artificial intelligence in clinical practice', which provides a framework for the safe and ethical integration of artificial intelligence (AI) into physician practice. The statement outlines core principles for implementing, interacting with and monitoring AI tools to ensure they enhance rather than replace clinical judgement, protect patient safety and privacy and abide by ethical and regulatory standards. It identifies important benefits, such as increased administrative efficiency and improved support for clinical decision-making, while cautioning against risks such as algorithmic bias, data breaches and medicolegal liabilities. The statement also offers enabling strategies to overcome various barriers such as biased or inaccurate tools, professional and public resistance to the use of AI and adverse environmental impacts. The RACP advocates for physicians to engage in AI development and implementation using an agile human-in-the-loop approach that prioritises patient safety, clinical governance, professional training and collaboration with stakeholders.